The comparative evaluation of the effectiveness of foreign capital in the capital of banks in Ukraine - Hirnyak, Vira (Ocena porównawcza efektywności udziału kapitału zagranicznego w kapitale sektora bankowego na Ukrainie, 2017)
Characteristic features of the manifestation of globalization and international integration in financial relations is the creation of international financial institutions, the entry of foreign capital into the national financial markets and strengthening its influence on the development of national financial systems. In Ukraine, the result of globalization and the international financial integration was the entry of foreign banks into the domestic financial markets by buying absorption of Ukrainian banks establishment by new banks with foreign capital. Among the main advantages of globalization environment is the liberalization of financial markets, the opening of national borders to the international movement of funds in global financial integration space and so on. Along with this in the context of globalization and openness of the national economy in a short period of time has been an increase of foreign capital in the capital of banks in Ukraine, which requires an assessment of the efficiency of capital in the total capital of the bank system and the new trends of the national banking system, introduced by the presence of foreign capital. On the basis of analysis of the indicators the assessment of the effectiveness of foreign capital in the capital of domestic banks was analyzed and positive and negative trends in their participation in the banking system of Ukraine were found. The main goal is comparative evaluation of the effectiveness of foreign capital in the capital of banks in Ukraine and the object are foreign banks in Ukraine. The main methods that are used in this article are statistics and calculations
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 19-30
Keywords: foreign capital; banking system; the European Union; efficiency; return on equity; return on assets; kapitał zagraniczny; system bankowy; Unia Europejska; efektywność; zwrot z kapitału własnego; zwrot z aktywów